Strategi Kampanye Caleg Kiagus Ishak (PAN) dan Syafruddin (PPP) dalam Pileg 2019 Kota Palembang - Zuhdi, Muhammad (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
Seeing from the phenomenon of legislative candidates who use various political campaign strategy methods used in competing in the legislative general election is very important, so in this study the author examines the problem of winning strategies that have been carried out by the incumbent legislative candidate from the PAN Party named Kiagus Ishak. Yasin and H. RM. Syafruddin, SE, .MM from the PPP Party as a new legislative candidate running where the two legislative candidates are both local male legislative candidates who come from Palembang aristocratic descent in winning the 2019 legislative elections in Palembang City what caused the success and the failure of the two legislative candidates. This study aims to determine the winning strategy used by the two candidates in their election area. Based on the theory used. The defensive strategy is used when the legislative candidates want to retain the majority or if the vote is achieved, they want to be preserved. This strategy was developed by legislative candidates as a way to maintain votes from the support surrounding the local community. The offensive political strategy is a political campaign strategy used to influence voters, what must be sold or displayed is the difference to the prevailing conditions at that time and the benefits that can be expected from it so that new voter groups can be formed in addition to existing voters. The results of the research conducted by the researchers, among others, were able to find that although both of them both bear the title of clan from the native area of ​​Palembang City, several factors were also found that led to the effectiveness of the strategies used by the two local male legislative candidates above, both Incumbent and incumbent candidates, namely Kiagus Ishak Yasin and a local legislative candidate, a local newcomer, H. RM. Syafruddin, SE, .MM so that it had a direct impact on the legislative candidates who won, namely Kgs Ishak Yasin from the PAN Party and there were also legislative candidates who failed to be elected or lost to H. RM. Syafruddin, SE, .MM from the PPP Party.